2022
DOI: 10.3389/fonc.2022.979519
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing the use of lenvatinib in combination with pembrolizumab in patients with advanced endometrial carcinoma

Abstract: IntroductionThe combination of lenvatinib plus pembrolizumab demonstrated a relevant clinical benefit in patients with endometrial carcinoma. The safety profile was consistent with the established profiles of each drug in monotherapy, with the most frequent adverse events being hypertension, an on-target effect, hypothyroidism, diarrhea, nausea, vomiting, loss of appetite, fatigue, and weight loss.Areas coveredWe first review the rationale based on the combination of a VEGFR inhibitor and an immune checkpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The most common grade ≥3 adverse events (AEs) in the combination therapy arm were hypertension (39.2%), decreased weight (10.8%), diarrhea (8.1%), and decreased appetite (7.6%) [ 12 ]. The safety profile of lenvatinib plus pembrolizumab was consistent with that reported in the phase 2 Study 111/KEYNOTE-146 [ 13 14 ] and those of the individual agents [ 15 ].…”
Section: Introductionsupporting
confidence: 79%
“…The most common grade ≥3 adverse events (AEs) in the combination therapy arm were hypertension (39.2%), decreased weight (10.8%), diarrhea (8.1%), and decreased appetite (7.6%) [ 12 ]. The safety profile of lenvatinib plus pembrolizumab was consistent with that reported in the phase 2 Study 111/KEYNOTE-146 [ 13 14 ] and those of the individual agents [ 15 ].…”
Section: Introductionsupporting
confidence: 79%
“…It has FDA approval as monotherapy and in combination with other drugs such as pembrolizumab or everolimus in the treatment of various types of cancers, including differentiated thyroid cancer (DTC), renal cell carcinoma (RCC), hepatocellular carcinoma (HCC), and EC. 151 Numerous studies have been conducted to investigate the effectiveness of lenvatinib as a monotherapy for EC. For example, the Vergote group studied the use of lenvatinib as a second-line treatment for patients with recurrent EC in 2019 and the results showed that it had a modest antitumor activity with a 14.3% ORR.…”
Section: Lenvatinibmentioning
confidence: 99%
“…It has FDA approval as monotherapy and in combination with other drugs such as pembrolizumab or everolimus in the treatment of various types of cancers, including differentiated thyroid cancer (DTC), renal cell carcinoma (RCC), hepatocellular carcinoma (HCC), and EC. 151…”
Section: Vegf Inhibitorsmentioning
confidence: 99%